Bevacizumab: A Rare Cause of Nonischemic Cardiomyopathy - Oladiran, Oreoluwa (Case Rep Cardiol, 2018)
Left ventricular dysfunction is a rare side effect of bevacizumab occurring in 2–4% of cases. We report the case of a 68-year-old woman who presented to the emergency department (ED) with sudden onset of shortness of breath, orthopnea, and paroxysmal nocturnal dyspnea. She was tachypneic and in respiratory distress. Physical examination revealed jugular venous distention, diffuse expiratory wheeze, and bipedal edema. She had been started on bevacizumab for the treatment of hereditary hemorrhagic telangiectasia 1 month prior to presentation. Laboratory tests revealed BNP of 1697 pg/ml with slightly elevated troponin 0.05 ng/ml. Chest X-ray showed interstitial edema with cardiomegaly, and transthoracic echocardiogram showed ejection fraction of 30% with global hypokinesia. Left heart catheterization revealed widely patent coronary arteries. Flash pulmonary edema secondary to acute left ventricular dysfunction in this case was attributed to recent treatment with bevacizumab after ruling out other possible etiologies. This case highlights the importance of early recognition of this rare but potentially reversible side effect of bevacizumab to prevent long-term sequelae.